Green Supplier Selection via an Integrated Multi-Attribute Decision_x000D_ Making Approach - KILIÇ, HÜSEYİN SELÇUK (My University, 2019)
The environmental awareness of society and the global competition market has increasedsignificantly due to the environmental problems that happen today. Companies have recognizedthe importance of focusing on environmental issues in order to be strong in a moderncompetitive business environment. Therefore, environmental factors are taken intoconsideration during the supplier selection process, which is an important decision point in thesupply chain. In this study, two robust multi-attribute decision making techniques, IntuitionisticFuzzy AHP (IF-AHP) and PROMETHEE, are used in an integrated way to better handle thisselection problem. The steps are clearly explained in the proposed methodology. First, therelative weights of the criteria are determined by IF-AHP, which allows decision makers (DMs)to deal with the uncertainty of the evaluation process. Subsequently, the weights of criteriaobtained are used in the PROMETHEE method for the best ranking of alternative suppliers. Anapplication is performed in the air filtration industry to demonstrate the validity of the proposedmethod.